Decreasing strabismus surgery. Issue 4 (17th March 2005) - Arora, A; Williams, B; Arora, A K; McNamara, R; Yates, J; Fielder, A
Abstract : Aim: To determine whether there has been a consistent change across countries and healthcare systems in the frequency of strabismus surgery in children over the past decade. Methods: Retrospective analysis of data on all strabismus surgery performed in NHS hospitals in England and Wales, on children aged 0–16 years between 1989 and 2000, and between 1994 and 2000 in Ontario (Canada) hospitals. These were compared with published data for Scotland, 1989–2000. Results: Between 1989 and 1999–2000 the number of strabismus procedures performed on children, 0–16 years, in England decreased by 41.2% from 15 083 to 8869. Combined medial rectus recession with lateral rectus resection decreased from 5538 to 3013 (45.6%) in the same period. Bimedial recessions increased from 489 to 762, oblique tenotomies from 43 to 121, and the use of adjustable sutures from 29 to 44, in 2000. In Ontario, operations for squint decreased from 2280 to 1685 (26.1%) among 0–16 year olds between 1994 and 2000. Conclusion: The clinical impression of decrease in the frequency of paediatric strabismus surgery is confirmed. In the authors' opinion this cannot be fully explained by a decrease in births or by the method of healthcare funding. Two factors that might have contributed are better conservative strabismus management and increased subspecialisation that has improved the quality of surgery and the need for re-operation. This finding has a significant impact upon surgical services and also on the training of ophthalmologists.